Health Nutrition and Sanitation Counseling Education in Improving Health Understanding in Sigapiton Village, Ajibata District, North Sumatra. - Rusdiana; Lubis, Nenni Dwi Aprianti; Savira, Maya; Widjaja, Sry Suryani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Healthy environmental sanitation and good nutrition are factors that determine human resources and quality of life. With healthy environmental sanitation, the community is protected from various infectious diseases and similarly with a good understanding of nutrition will produce individuals with good quality. For this reason, it is important to achieve resources and good quality of life. This understanding is enhanced by providing health education. and good nutrition so that people are protected from various diseases. Health matters are matters of the environment, attitudes and behavior of the community. One of the causes of this nutritional deficiency is stunting, namely short stature in which a child who is stunted produces a low level of intelligence. For this reason, it is necessary to educate the public to understand the importance of good nutrition for children's growth. There is a wrong perception in the general public that stature is a hereditary factor, not a factor in malnutrition so that they do not pay attention to the nutritional status of children. Wrong choice of food for consumption, as well as nutritional balance between intake and output of substances (nutritional imbalance), namely intake that exceeds output or vice versa is the result of nutritional problems that occur in toddlers. This causes several impacts, including chronic disease, overweight and underweight, pica, dental caries, and allergies. For this reason, in this case the community service team wants to provide education about counseling to the community where the targets to be carried out are pregnant women, school children and young women. During the Covid 19 pandemic, the targets we educate are through cadres and village officials, this is to avoid infection with the covid 19 virus. By providing counseling to cadres and village officials, we hope that it will reach the people of Sigapiton village. Where in this counseling we provide pocket books to the cadres and village officials that we educate. We hope that this service can increase public knowledge about nutrition understanding and the creation of healthy environmental sanitation. We will publish the output of this service in an international journal indexed by Scopus